Tomato LrgB regulates heat tolerance and the assimilation and partitioning of carbon. (September 2018) - Zhang, Shiwen; Ai, Guo; Li, Miao; Ye, Zhibiao; Zhang, Junhong
Highlights: SlLrgB contributes to chlorophyll metabolism and chloroplast development. SlLrgB and Hsc70.1 play important roles in heat tolerance. Hsc70.1 negatively regulates SlLrgB and vice versa . SlLrgB regulates the assimilation and partitioning of carbon. SlLrgB regulates chlorophyll biosynthetic pathway. Abstract: The impact of extreme and sustained high temperatures on plant growth has become increasingly prominent. Heat shock cognate 70-kDa proteins play an important role in plant heat tolerance. In this study, we identified and characterized the tomato ortholog of LrgB ( SlLrgB ), and demonstrate that it interacts with Hsc70.1. Similar to other genes that encode chloroplast-localized proteins, the expression of SlLrgB is upregulated in green tissues and suppressed by heat shock. Functional analyses utilizing transgenic plants indicate that SlLrgB contributes to chlorophyll metabolism. Both the overexpression and the RNA interference-mediated suppression of SlLrgB led to chlorotic leaves, reduced plant height, smaller size and decreases in pigment levels in ripening fruits. However, the starch levels in the SlLrgB -RNAi lines were significantly increased and the heat tolerance of SlLrgB -RNAi was obvious elevated. Downregulating the expression of Hsc70.1 by VIGS in tomato led to retarded growth, chlorotic leaves, and increased expression of SlLrgB. Based on these data, we suggest that SlLrgB regulates chlorophyll metabolism and the assimilation and partitioning of carbon. We also suggest that Hsc70.1 and SlLrgB contribute to heat tolerance and that Hsc70.1 negatively regulates SlLrgB .